Improving glycemic control: transitioning from dulaglutide to tirzepatide in patients with type 2 diabetes undergoing hemodialysis - Emiko Otsuka; Emiko Otsuka; Mineaki Kitamura; Mineaki Kitamura; Satoshi Funakoshi; Hiroshi Mukae; Tomoya Nishino (Frontiers Media S.A., 2024)
Background: Tirzepatide-a dual glucose-dependent insulinotropic peptide and glucagon-like peptide-1 receptor agonist-is used to treat type 2 diabetes. However, the efficacy and safety of tirzepatide in patients undergoing hemodialysis remain unclear.Methods: We conducted a single-center retrospective study of patients with type 2 diabetes undergoing hemodialysis who were transitioned from dulaglutide to tirzepatide. We continuously monitored glucose levels in patients undergoing hemodialysis before and after switching from dulaglutide to tirzepatide.Results: Fourteen patients (mean age: 61.9 ± 9.9 years, male: female = 11:3) were included in this study. After switching to tirzepatide, time in range increased to 50.8% from 42.7% (p = 0.02), time above range decreased to 37.8% from 48.4% (p = 0.02), and mean glucose levels decreased to 137.4 mg/dL from 156.6 mg/dL (p = 0.006). In contrast, there was no significant difference in time below range before and after tirzepatide administration (11.3% and 8.9%) (p = 0.75). Three patients experienced dyspepsia (21.4%), and one patient experienced nausea (7.1%); however, no critical adverse events were reported.Conclusion: Transitioning from dulaglutide to tirzepatide improved glycemic control without increasing hypoglycemia in patients undergoing hemodialysis for type 2 diabetes.